Pengaruh DER terhadap ROE Perusahaan Sub Sektor Tekstil dan Garmen Yang Terdaftar di BEI 2015-2019 - Silvira Agustina; Hasbi Assidiki Mauluddi; Rosma Pakpahan (Indonesian Journal of Economics and Management, 2021)
The aim of this research is to examine the influence of Debt to Equity Ratio (DER) towards Return On Equity (ROE) on Textile and Garment Industry Company Listed on The Indonesia Stock Exchange 2015-2019. This research uses asosiative method with quantitative approach. This research using secondary data from annually company report. The analysed data is using panel data regression with the assistance of Eviews version 10. The result of this research shows that Debt to Equity Ratio (DER) has positive and significant influence toward Return on Equity (ROE).